2005
DOI: 10.1128/jcm.43.4.1699-1705.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Variable-Number Tandem Repeats To Examine Genetic Diversity of Neisseria meningitidis

Abstract: Repetitive DNA motifs with potential variable-number tandem repeats (VNTR) were identified in the genome of Neisseria meningitidis and used to develop a typing method. A total of 146 meningococcal isolates recovered from carriers and patients were studied. These included 82 of the 107 N. meningitidis isolates previously used in the development of multilocus sequence typing (MLST), 45 isolates recovered from different counties in Norway in connection with local outbreaks, and 19 serogroup W135 isolates of seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
46
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…In these complexes, the same patterns were obtained for epidemiologically related isolates from a relatively confined area and during a limited period of time (15). Therefore, the VNTR diversity demonstrated in the ST-162 complex in Greece suggests that this clonal complex has circulated for some time in the country and that the diseaseassociated isolates do not represent an outbreak situation.…”
mentioning
confidence: 50%
See 3 more Smart Citations
“…In these complexes, the same patterns were obtained for epidemiologically related isolates from a relatively confined area and during a limited period of time (15). Therefore, the VNTR diversity demonstrated in the ST-162 complex in Greece suggests that this clonal complex has circulated for some time in the country and that the diseaseassociated isolates do not represent an outbreak situation.…”
mentioning
confidence: 50%
“…We have previously demonstrated that VNTR typing is capable of distinguishing between meningococcal isolates belonging to the ST-32 complex and those belonging to the ST-11 complex (15). In these complexes, the same patterns were obtained for epidemiologically related isolates from a relatively confined area and during a limited period of time (15).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…MLVA has been used to subtype a variety of species of bacteria, some of which have been difficult to subtype by other methods. Bacteria that have been typed by MLVA include Salmonella serotypes Typhimurium (22,24,35) and Typhi (26), Yersinia pestis (19), Francisella tularensis (9,17), Mycobacterium tuberculosis (1), Haemophilus influenzae (41), Bacillus anthracis (18), Bordetella pertussis (40), Escherichia coli O157:H7 (23,31), Enterococcus faecalis (47), Neisseria meningitidis (51), and Pseudomonas aeruginosa (33). MLVA has proven to be a rapid method and may be easy to standardize between laboratories.…”
mentioning
confidence: 99%